THE IMPACT OF OPENNESS ECONOMIC AND ISLAMIC DEVELOPMENT BANK PROJECTS ON ECONOMIC GROWTH IN THE ALGERIA ECONOMY - Mahfoudi, Fouad; Riache, Siham; Chahdi, Fawzi; Riache, Mabrouk; Louail, Bilal (The journal of contemporary issues in business and government, 2024)
This study aims to illustrate the importance of IDB projects in developing economic growth in Algeria through economic openness. This study used the multiple regression of Algeria's economy from 1980-2022. The study found a positive and significant impact of FDI, per capita, and total population growth on Algeria's economic growth and a negative impact of inflation on growth. Through the results of this study, decision-makers in Algeria's economy can rely on this study to develop their economies through IDB projects. Researchers and academics can also benefit from the results of this study as a study that opens up new prospects for the topic in the future.